Are Slovenia’s forests deviating from sustainable development? - Kušar, Gal (Acta silvae et ligni, 2023)
This paper provides an overview of the sustainable development of Slovenian forests between 2000 and 2018. The state and development of Slovenian forests in terms of sustainability were examined using a set of variables and indicators of sustain able forest management such as forest area, basal area, growing stock, stand density index, age structure/diameter distribu tion, demographic balance, optimal growing stock, increment, felling, species diversity, species mixture, forest regeneration, naturalness and deadwood. We also assessed the suitability of the systematic 4 x 4 km sampling grid. All estimates were calcu lated at the national, ecoregional and forest region levels. In 2018, forest cover was estimated at 60% and was slightly higher than that in 2012. Conversely, growing stock volume decreased and was estimated at 329.6 m3 /ha. Young forests accounted for 29%, older forests for 68% and uneven-aged forests for 3% of the total forest area. Beech and spruce were the dominant tree species. The proportions of other species were less than 10%, and concerns were raised about their recruitment. Comparative analyses of the desired values of the indicators and the values reported by the Forest Europe process member states and some selected countries raised doubts about Slovenia’s progress towards sustainable forest development. Furthermore, the 2018 dataset does not fully support the indicators of sustainable forest management.
Keywords: časovna analiza; indicators; kazalniki; Slovenia; Slovenija; sustainable forest management; temporal analysis; trajnostno gospodarjenje z gozdovi